The Effect of the Illustrated Storybook-Assisted Literacy Approach on Students' Reading Comprehension Ability in Grade V - Pramesti, Mudita; Cahyaningtyas, Andarini Permata (Research, Training and Philanthropy Institution Natural Aceh, 2025)
Reading comprehension is a fundamental skill essential for learning success at the elementary school level. This skill enables students to comprehend the content of texts, identify the main ideas, and relate the information in the text to their prior knowledge or experiences. However, many students still struggle to thoroughly comprehend texts. Low reading interest and limited access to engaging learning media remain significant obstacles to developing literacy skills. This study aims to examine the Effect of a literacy approach assisted by picture storybooks on the reading comprehension ability of fifth-grade students at SD N Purwoyoso 01 and SD N Purwoyoso 03. The research employed a quantitative approach using a quasi-experimental design with two groups: an experimental group and a control group. Data were collected through observation, interviews, documentation, and pre-and post-test assessments. The results showed a significant improvement in the experimental group after implementing the picture storybook-assisted literacy approach compared to the control group. Picture storybooks helped students better understand the texts enjoyably by integrating visual, oral, and written literacy. This approach proves to be an effective alternative for improving reading comprehension in Indonesian language learning at the elementary school level.